Factors influencing liveweight in a range of network situations - Maehl, J.H.H.; Coulibaly, L.; Defly, A.; D'Ieteren, G.D.M.; Feron, A.; Grundler, G.; Hecker, P.; Itty, P.; Mawuena, K.; Morkramer, G.; Mulungo, M.; Nagda, S.M.; et al. (1988)
The health and performance records of cattle and sheep used were collected over a three-year period, 1984-1986, at four network sites. Three of the sites, Avetonou (Togo), Boundiali (Cote d’Ivoire) and Mushie (Zaire) were chosen because of their high mean trypanosome of the live weight performance, and the fourth site, Kolo (Zaire), was chosen to give estimates of the liveweight performance of trypanotolerant cattle at zero trypanosomiasis risk. Trypanosome prevalence significantly depressed the live weight performance of N’Dama cattle at Mushie, but the effects at the other sites, although generally in the same direction as those at Mushie, did not reach statistical significance (p>0.05). At Mushie trypanosome infection of the N’Dama cow during gestation did not affect her parturition weight, but in the infection occurred during the last 3 months pre-partum then the birth weight of her calf was depressed significantly. The results relating PCV & live weight traits showed that a low PCV associated with poor live weight performance and a high PCV with better performance. Result from the Mushie, Kolo and Avetonou showed a positive relationship of mean PCV in the calf pre-weaning with pre-weaning growth and weaning weight. Trypanosome infection in the ewe, as measured by the number of parasitaemic months during gestation and/or lactation, did not depress her subsequent body weight, nor was there any cumulative effect of trypanosome infection pre and post-partum on ewe weight at weaning, nor on ewe weight change during the lactation, Similarly lamb weaning weight and lamb pre-weaning growth were not affected lamb weaning weight and lamb pre-weaning growth were not affected by one or more parasitaemic months in the ewe during lactation.